Einige Probleme der zeitgenössischen Biozönologie und ihre Lösung bei agrarentomologischen Studien. - Giljarov, Merkurij Sergeevitsch (Contributions to Entomology = Beiträge zur Entomologie, 1961)
1. The formation of bioeeonoses is determined by natural selection as like as the evolution of species. - 2. The population (the totality of individuals of a given species belonging to a given concret biocoenosis) is the fundamental structural unit of both the species and the biocoenosis. - 3. Natural selection primary appears as succession, i. e. succession of species in biocoenoses, which is induced above all by the activity of the biocoenosis itself. - 4. By changes of local conditions in the biocoenosis observed in the course of succession i he population becomes either extinct if these changes exceed the ecologic plasticity of a given population (rarely the population becomes severely modified by adaption to the changes in succession) or the population survives by migration of a part of the individuals to new places where the conditions correspond the demand of this population. By lliis way the insufficient plasticity of a species is compensated by the dispersal capacity. - 5. At rapid changes in vegetation by rotation of crops among injurious insects only lhe polyphagous ones and oligophagous species with short life cycle and high dispersal capacity will survive. Selection takes place as to qualities which are closely connected with changing factors (changes in vegetation - degree of polyphagy) and also as to qualities which are only indirectly connected with those factors (ability te dispersal). - 6. Selection peculiarities in natural successions of biocoenoses can be studied by comparison with rotation of crops.